Amphibian conservation using assisted reproductive technologies: Cryopreserved sperm affects offspring morphology, but not behavior, in a toad - Sinlan Poo; Kristin M. Hinkson (Global Ecology and Conservation, 2020)
With increasing rates of global biodiversity decline, strategies such as reintroduction or supplementation, have become increasingly important in conserving our remaining biodiversity. To sustain reintroduction programs, insurance colonies are established and bred in captivity. Captive-bred offspring are then released to augment wild populations or establish new populations. A key issue determining the success of reintroduction programs, therefore, is the fitness of captive-bred individuals and their ability to survive once released. Unfortunately, little is known about the quality of captive-bred offspring produced using assisted reproductive technologies, such as gamete cryopreservation. To fill this gap in scientific knowledge and conservation practice, we examined differences in tadpole morphology, tadpole behavior, metamorph morphology, and duration of larval stage between Fowler's toad (Anaxyrus fowleri) offspring produced using cryopreserved sperm (experimental, cryo-derived individuals) and offspring produced by amplectant adults (control individuals). Results indicated cryo-derived individuals were smaller as tadpoles and emerged as smaller metamorphs. However, predator-avoidance behavior was not significantly different between the two treatment groups. Smaller body size in cryo-derived individuals can negatively affect their post-release survivorship and reproductive output, thus limiting the potential success of reintroduction programs. This pioneering study provides insights into the quality and competency of individuals produced using cryopreserved sperm across two distinct life-stages. We show that although cryopreservation has often been proposed as a promising way of contributing to wildlife conservation, more detailed examinations are needed to assess the quality of offspring produced for it to be an effective conservation tool. Keywords: Anura, Bufonidae, Gamete cryopreservation, Carry-over effects, In vitro fertilization